Potential social media campaign challenge towards physical activity in modern era - Nurlienda Hasanah; Hafidhotun Nabawiyah; Yeni Tri Herwanto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Physical inactivity is one of the leading risk factor for non-communicable diseases in the world. Globally, the insufficient of physical activity is experienced by 25% of adults and 80% of adolescents. The lifestyle of adolescents and adults are increasingly tied to social media. More than 87% of netizens in Indonesia access social media. Social media is used to communicate and it can form social support including healthy behavior awareness. The aim of this study is to explore netizens response on Promkes.net social media campaign “#7HariMelawanMager” challenge (Seven-days challenge beat physical inactivity). This study was a literature review, using supported document and challenge mini-survey on Instagram story and Facebook polling in a day and interview with challenge’s founder. As the result in three weeks, after the #7HariMelawanMager challenge launched, there were 41 posts in Instagram with 9 netizens completed and 33 posts in Facebook with 13 netizens completed the challenge. The social media challenge raising physical activity awareness from the community. Yet there were 17 netizens who fulfill the @promkes_net Instagram story survey and 5 of 15 netizens did not know the campaign through Facebook’s author polling. At the end of the review, there are 98 netizens joining “Melawan Mager” Pacer group. Health campaigns through social media #7HariMelawanMager have the potential to increase awareness of physical activity. However, this campaign needs to consider the sustainability. Furthermore, netizens will better understand the benefits of physical activity to improve their quality of life.